Peningkatan Kosakata Siswa Dalam Bahasa Inggris Di SMP Negeri Satap Pulau UT Kota Tual - syamsinar inar; Ahmad Thariq (LP3M Universitas Muhammadiyah Sorong, 2023)
Learning is a collaborative process involving students and teachers who design every activity that will be carried out to help students understand and master the subject matter. So that in carrying out their duties, teachers are required to create a classroom atmosphere that allows students to understand the material presented well. However, in reality the teaching and learning process does not always go as expected. In the teaching and learning process, problems often arise that may hinder the smooth running of the teaching and learning process itself. English is a challenge for students to learn because they lack vocabulary, and there is no appropriate learning method to teach students to master vocabulary quickly and precisely in English. For this reason, several learning media were used, namely English flashcards, translating song, the knowledge tree, motivation wall and the crossword puzzle. By applying several media and methods, it is hoped that it can improve students' vocabulary in English at SMPN Satap 4 Tual.